Coming Home to Sugar Lake - Adair, Marina (New York Made available through hoopla, 2014)
From the author of the nationally bestselling St. Helena Vineyard series and the Heroes of St. Helena series comes the sexy first book from Marina Adair set in Sugar, Georgia... Hes trouble she doesnt need... Thanks to a cheating fiance Josephina Harringtons perfect life just crashed and burned. Moving in with her overbearing parents is definitely not an option. No, she needs to prove she can make it on her own. And she will - by turning her great-aunts old plantation house into a destination getaway. Shes just not expecting her contractor to be so hands-on - and so totally irresistible... but everything she wants Bad-boy golf champion Brett McGraw figured his hometown of Sugar, Georgia, was the perfect place to lay low and get his life back up to par. The leggy blonde with a pint-sized pup is the kind of sweet n sassy trouble he never saw coming. She doesnt know a nut from a bolt and before long, hes renovating her house... as she steals his heart. Can he convince Josephina that his womanizing ways are in the past and hes ready for forever?
Keywords: Man-woman relationships -- Fiction; Georgia -- Fiction; Romance fiction